2015
DOI: 10.1002/jhet.2551
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of New 1‐(4‐Methylpiperazin‐1‐yl)thioureas as Potential Antitubercular Agents

Abstract: Synthesis, characterization, and preliminary biological assessments of compounds with antitubercular activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The synthesis of all asymmetric thioureas with the fragment of N-methylpiperazine is based on the classical reaction of the interaction N-methyl-N 1 -aminopiperazine with the corresponding aromatic isothiocyanates [9,10]. We have shown that asymmetric thioureas 5a-e can be obtained by the condensation of N-methyl-N 1aminopiperazine 4 with the corresponding N 1 -aryl-N,Ndimethylthioureas 3a-e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of all asymmetric thioureas with the fragment of N-methylpiperazine is based on the classical reaction of the interaction N-methyl-N 1 -aminopiperazine with the corresponding aromatic isothiocyanates [9,10]. We have shown that asymmetric thioureas 5a-e can be obtained by the condensation of N-methyl-N 1aminopiperazine 4 with the corresponding N 1 -aryl-N,Ndimethylthioureas 3a-e.…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial [3], antifungal [4,5], anti-inflammatory, analgesic and kinase CDK1 inhibition [6,7] activities are reported for iminothiazole-containing heterocyles. N-methylpiperazine derivatives containing the azole nucleus possess the antifungal [8], antituberculosic [9,10] and antimicrobial [9] activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar vein, compound (94m) had a diameter of inhibition higher than 10 mm at 200 μg. (Scheme 19) [34] Amaroju Suresh et al designed, synthesized, and tested new substituted sulfonamide tetrazole derivatives as antitubercular agents. As shown in Scheme 20, the proposed compounds were synthesized in seven steps.…”
Section: Ms Komal Saini Has Been Working As Anmentioning
confidence: 99%
“…In a similar vein, compound (94m) had a diameter of inhibition higher than 10 mm at 200 μg. (Scheme 19) [34] …”
Section: Chemistry Of Different Heterocycle Scaffolds As Antitubercul...mentioning
confidence: 99%